2010
DOI: 10.1111/j.1744-6163.2010.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Post-Seclusion Debriefing: A Core Nursing Intervention

Abstract: A post-seclusion debriefing framework needs to be developed to support best practice in managing seclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 46 publications
3
30
0
2
Order By: Relevance
“…Based on these results, we may ascertain that PSRR with the patient was not previously part of the staff's usual practice. This corroborates Needham and Sands’ retrospective file audit, which revealed that only 1 out of 63 files had evidence of PSRR explicitly related to SR. Our participatory study allowed overcoming the perceived discomfort of all parties by systematizing PSRR with the patient.…”
Section: Discussionsupporting
confidence: 84%
“…Based on these results, we may ascertain that PSRR with the patient was not previously part of the staff's usual practice. This corroborates Needham and Sands’ retrospective file audit, which revealed that only 1 out of 63 files had evidence of PSRR explicitly related to SR. Our participatory study allowed overcoming the perceived discomfort of all parties by systematizing PSRR with the patient.…”
Section: Discussionsupporting
confidence: 84%
“…Although one study found that forensic staff believe debriefings to be necessary (Gustafsson & Salzmann‐Erikson ), several patients in the current study perceived that staff refrained from debriefing them. This is in line with Needham and Sands (), who showed that debriefings following seclusion were not routinely performed. According to the results from this current study, a lack of or inadequate debriefing resulted in patients maintaining ‘silent protest reactions’, whereas a consistent debriefing provided patients with an understanding of staff's reasons for both the use and duration of the MR episode, and supported patients being ‘genuinely calm’.…”
Section: Discussionsupporting
confidence: 89%
“…(), this could be due to memory loss in some cases. However, Needham and Sands () conducted a retrospective file audit and concluded that debriefing was not routinely performed. Nevertheless, those patients in the included studies who remembered having a professional conversation perceived it to be helpful and calming, or specifically necessary to avoid trauma.…”
Section: Discussionmentioning
confidence: 99%